Clinical Genetic Testing in Children with Kidney Disease - Eungu Kang; Beom Hee Lee (Korean Society of Pediatric Nephrology, 2021)
Chronic kidney disease, the presence of structural and functional abnormalities in the kidneys, is associated with a lower quality of life and increased morbidity and mortality in children. Genetic etiologies account for a substantial proportion of pediatric chronic kidney disease. With recent advances in genetic testing techniques, an increasing number of genetic causes of kidney disease continue to be found. Genetic testing is recommended in children with steroid-resistant nephrotic syndrome, congenital malformations of the kidney and urinary tract, cystic disease, or kidney disease with extrarenal manifestations. Diagnostic yields differ according to the category of clinical diagnosis and the choice of test. Here, we review the characteristics of genetic testing modalities and the implications of genetic testing in clinical genetic diagnostics.